The Construction of Assembly semantic model AHGD-F Based on Functional Components and the Analysis of Polychromatic Assembly Compatibility - Xiaoxi Kou, Yan Cao, Hu Qiao (Forest Chemicals Review)
With the rapid development of intelligent manufacturing, the data demand of assembly planning for product model tends to be diversified, standardized and accurate. Assembly model is the key to the expression of assembly semantics. The assembly hybrid G-diagram (AHGD), a model containing the semantics of assembly linkage and assembly priority relationship and capable of data transformation, is constructed based on the assembly structure of the product. From the perspective of part attributes, the functional parts are regarded as the main nodes of the assembly semantic model combined with the star topology to construct the assembly hybrid G-diagram based on functional parts (AHGD-F), which provides a visual model and data basis for subsequent intelligent planning under the premise of ensuring product functions. The assembly compatibility of AHGD-F model is analyzed by multicolor principle, so as to meet the requirements of assembly feasibility and ensure the functionality of assembly semantic model. The assembly semantic expression of AHGD-F model is verified by milling fixture, and the multi-color assembly compatibility analysis is carried out to provide effective assembly semantic verification for subsequent assembly sequences. The construction of visual assembly semantic model can clearly reflect the assembly relationship of product parts. The mapping and conversion of model and data provide reference and data information for later intelligent assembly, which can effectively reduce the error probability of assembly relationship data input.